Heart rate variability during different training periods in 17 elite swimmers - Lacoste, L.; Caudal, N.; Vanoorenberg, P.; Schmitt, L.; Fauquet, C.; Cervetti, J. P.; Rey, J. L.; Hellard, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Heart rate variability (HRV) analysis is a well recognized method to assess autonomic nervous system perturbations and was shown to be influenced by the fitness and the fatigue in endurance athletes (Pichot et al., 2000). Increase in sympathetic tone was chronically experienced by athletes who were overtrained due to an intense anaerobic training regimen. In contrast, parasympathetic tone predominated in athletes who increased the training volume to a great extent (Hedelin et al., 2000). In swimming, a linear model of periodization characterized the training cycles (Avalos et al., 2003): each training cycle, lasting between 8 and 12 weeks, commenced with high training volume and low intensity. As training progressed, volume decreased and intensity increased. The aims of this study were, first, to compare HRV during pré season (PS), aerobic (AP), high intensity (HP), and taper (T) phases. Method RR intervals were recorded every Saturday (9 am) during a 10 min supine position by using a Polar® S810 heart rate monitor. We used the Burg`s method with a ten order model. RR intervals are first interpolated with cubic splines in order to resample the signal with 1 Hz frequency. The mean HR, the standard deviation of all R-R intervals (SDNN) and the percentage of successive interval differences larger than 50 ms (PNN 50) were used as time-domain measures of HR variability. Peaks are then extracted from the spectrum and determined on very low frequency (VLF between 0.00 Hz and 0.04 Hz), low frequency (LF between 0.04 Hz and 0.15 Hz) and high frequency (HF between 0.15 Hz and 0.5 Hz). This allows us the determination of total (TP), VLF, LF and HF powers and computing the LF/HF ratio. Results TP, VLF and LF were lower (p < 0.05) in (PS) (9859, 3615 and 2251 ms².hertz-1) than in (T) (26651, 16931, and 5042 ms².hertz-1). After (HP), TP, LF and VLF increased during taper phase (9044, 4202 and 1907 ms².hertz-1, vs. 26751, 16931 and 5042 ms².hertz-1). Discussion and conclusion Autonomic nervous system status depends on adaptation due to different training phases. Total autonomic nervous tone, very low frequency, low frequency increased during (AP) (ns), decreased during (HP) and rebounds during (TP). These results suggest a sympathetic system inhibition during (HP) interpreted as the consequence of training volume (Hedelin et al., 1998) and total psycho-emotional stress (Kuipers, 1998).